PENGGUNAAN LKS BERBASIS PENDEKATAN SAINTIFIK DI SEKOLAH DASAR SELAMA PANDEMI COVID-19 - Susana Dawut; Marselinus Robe; Heronimus E A. Wejang (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
This paper aims to explore the use of scientific-based worksheets in elementary schools during the Covid-19 pandemic. Specifically, this paper explores two things: the importance of using scientific-based worksheets in learning in elementary schools during the covid-19 pandemic; and how to use the worksheets. This research used the library method. In this literature study, the research team collected in-depth information and data through various literatures, books and journal articles, as well as relevant previous research results. The results showed that: first, the importance of the worksheets in elementary schools, namely (a) students actively construct concepts, laws or principles through the stages of scientific learning; (b) able to be active and enthusiastic in learning. (c) encourage students to become “researchers”, think scientifically, critically and analyze. (d) students are able to formulate a problem (by asking a lot of questions), not only solving problems by answering, but students are required to ask questions. Second, the use of the worksheets is as follows: the first thing to do in developing the worksheet is by compiling a scientific-based worksheets design, then testing and the using them, and the last step is making cover, introduction, instructions for using worksheets, table of contents, book menus, concept maps and learning activities. From the results of the research above, it is concluded that the importance of using scientific-based worksheets in learning in elementary schools during the covid-19 pandemic is to attract active students and enthusiasm in learning, encourage students to become